Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1001/jama.2018.0438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meropenem-Vaborbactam vs Piperacillin-Tazobactam on Clinical Cure or Improvement and Microbial Eradication in Complicated Urinary Tract Infection

Abstract: clinicaltrials.gov Identifier: NCT02166476.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
204
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(219 citation statements)
references
References 19 publications
2
204
1
5
Order By: Relevance
“…Gram-negative pathogens is an especially serious threat given the limited treatment options available for patients with these infections (1,2). While new drugs, such as ceftazidime-avibactam, meropenem-vaborbactam, and ceftolozane-tazobactam, have provided much-needed additions to the current antibiotic armamentarium, some pathogens display resistance to these new ␤-lactam combination agents (3)(4)(5). The most significant of these resistant pathogens are multidrug-resistant Pseudomonas aeruginosa, multidrug-resistant Acinetobacter baumannii, and Enterobacteriaceae with metallo-␤-lactamases (MBLs) such as New Delhi MBL (NDM) (6)(7)(8).…”
mentioning
confidence: 99%
“…Gram-negative pathogens is an especially serious threat given the limited treatment options available for patients with these infections (1,2). While new drugs, such as ceftazidime-avibactam, meropenem-vaborbactam, and ceftolozane-tazobactam, have provided much-needed additions to the current antibiotic armamentarium, some pathogens display resistance to these new ␤-lactam combination agents (3)(4)(5). The most significant of these resistant pathogens are multidrug-resistant Pseudomonas aeruginosa, multidrug-resistant Acinetobacter baumannii, and Enterobacteriaceae with metallo-␤-lactamases (MBLs) such as New Delhi MBL (NDM) (6)(7)(8).…”
mentioning
confidence: 99%
“…Prospective randomized controlled trial data further support that TZP alone is not overtly damaging to the kidney. For instance, when TZP was compared to meropenem-vaborbactam in 545 patients with urinary tract infections, TZP was reported in adverse events to increase SCr a rate of 0.4% vs. 0% in meropenem-vaborbactam (46). In a separate large trial of 391 patients comparing TZP vs. meropenem for resistant Gram-negative bloodstream infections, TZP only resulted in n=1 non-fatal serious adverse event with increased creatinine vs. n=0 for meropenem (47).…”
Section: Discussionmentioning
confidence: 99%
“…As part of the 21st Centuries Cures Act, the Limited Population Antimicrobial Drug pathway emerged allowing for smaller, more feasible trials in limited populations [71]. The recent positive opinion adopted by the Committee for Medicinal Products for Human Use on meropenem/vaborbactam for the treatment of cUTI, cIAI and HAP/VAP on the basis of a large Phase III study in cUTI [72], and a study in 77 subjects with confirmed or suspected CRE infection at a range of body sites [42], further demonstrates the welcome and forward-thinking approach by regulators to help address the challenge of antimicrobial resistance (AMR). Many other active and expert groups continue to propose innovative approaches to clinical trials [73,74].…”
Section: Innovation and Stewardshipmentioning
confidence: 99%